The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ggi.14199
|View full text |Cite
|
Sign up to set email alerts
|

Thiol–disulfide homeostasis and ischemia‐modified albumin as a marker of oxidative stress in patients with sarcopenia

Abstract: Sarcopenia is characterized by progressive and generalized loss of skeletal muscle mass and strength. Chronic inflammatory conditions and increased oxidative stress are in the pathogenesis of sarcopenia. Our aim was to evaluate the relationship between sarcopenia and thiol-disulfide homeostasis and ischemia-modified albumin levels as an oxidative stress marker.Methods: Patients aged ≥65 years were recruited in this study. Sarcopenia was diagnosed according to the European Working Group on Sarcopenia in Older P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Moreover, Erel et al reported that thiol-disul de balance deteriorated in diseases characterized by intense in ammation and oxidative stress, such as hypertension, diabetes, metabolic syndrome and burns 33 . Therefore, although the albumin level of patients with sarcopenia should be lower than that of patients without sarcopenia in theory, it is actually affected by comorbidities and other factors, which has been reported in previous studies 34,35 .…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, Erel et al reported that thiol-disul de balance deteriorated in diseases characterized by intense in ammation and oxidative stress, such as hypertension, diabetes, metabolic syndrome and burns 33 . Therefore, although the albumin level of patients with sarcopenia should be lower than that of patients without sarcopenia in theory, it is actually affected by comorbidities and other factors, which has been reported in previous studies 34,35 .…”
Section: Discussionmentioning
confidence: 71%
“…It may be because of the fact that oxidative pathways have been stimulated as the disease progresses, which means that antioxidant effectors, such as thiols, will be depleted to buffer the oxidative stress [ 41 ]. In addition, proteinuria in women with PE leads to albumin loss, and as albumin is the main carrier protein for thiol groups in the plasma, total and native thiol concentrations may reduce subsequently [ 42 ]. These findings may also explain the findings of some previous clinical studies that supplementation with some antioxidants may be effective in reducing the incidence of PE in high-risk women [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%